Síntese de antena duplo refletora com diagrama de radiação ISOFLUX - Helvécio de Almeida Júnior (2022)
This work presents the formulation and synthesis for the circularly symmetric dual-reflector Cassegrain and its aperture field, which, according to the principles of Geometrical Optics (GO), radiates an electromagnetic field with a ISOFLUX pattern. Such ISOFLUX pattern is capable, in principle, of compensating the spatial attenuation associated with the coverage offered by antenna embedded in a satellite, providing uniform coverage over the Earth’s surface The syntheses of the aperture field and, later, of the reflective surfaces are based on the GO principles. For this, it is assumed that the dimensions (diameters) of the reflectors are much larger than the wavelength. This work presents as a contribution the addition of the blockage caused by the sub-reflector in the formulation found in the literature. This work also replaces one of the equations in the formulation used as basis for the dual-reflector synthesis, by another that ensures the continuity of the phase over the aperture area. Four examples of Cassegrain antenna synthesis with ISOFLUX patterns are investigated. As the syntheses of the aperture field and the reflectors do not take into account diffractive effects on the edges of the reflectors and mutual coupling between reflectors, a more rigorous analysis, based on the Method of Moments (MoM), is performed on the synthesized antennas, with the aim of to validate the results obtained.